Functions of Group 2 Innate Lymphoid Cells in Tumor Microenvironment - Xiong, Jia; Wang, Haofei; He, Jia; Wang, Qingqing (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs), defined as a heterogeneous population of lymphocytes, have received much attention over recent years. They can be categorized into three subsets according to the expression profiles of transcription factors and differing levels of cytokine production. These cells are widely distributed in human organs and tissues, especially in mucosal tissue. The ILCs are involved in various physiological and pathological processes, including inflammation, worm expulsion, autoimmune disease and tumor progression, many of which have been investigated and clarified in recent studies. In the tumor microenvironment, group 2 innate lymphoid cells (ILC2s) have been proved to be able to either promote or inhibit tumor progression by producing different cytokines, recruiting diverse types of immune cells, expressing immunosuppressive molecules and by regulating the expression of certain inflammatory factors. This review summarizes recent research progress on the immunomodulatory functions of ILC2s in the tumor microenvironment and puts forward some perspectives for future study.